Advanced Understanding of Monogenic Inflammatory Bowel Disease - Nambu, Ryusuke; Muise, Aleixo M. (Frontiers in Pediatrics, 2021)
Inflammatory bowel disease (IBD) is a group of chronic disorders that cause relapsing inflammation in the gastrointestinal tract and comprise three major subgroups of Crohn's disease (CD), ulcerative colitis (UC), and IBD-unclassified (IBDU). Recent advances in genomic technologies have furthered our understanding of IBD pathogenesis. It includes differentiation rare monogenic disorders exhibiting IBD and IBD-like inflammation (monogenic IBD) from patients with the common polygenic form of IBD. Several novel genes responsible for monogenic IBD have been elucidated, and the number of reports has increased due to advancements in molecular functional analysis. Identification of these pathogenic genetic mutations has helped in elucidating the details of the immune response associated with gastrointestinal inflammation and in providing individualized treatments for patients with severe IBD that is often unresponsive to conventional therapy. The majority of monogenic IBD studies have focused on young children diagnosed <6 years of age (very early-onset IBD); however, a recent study revealed high prevalence of monogenic IBD in older children aged >6 years of age as well. Meanwhile, although patients with monogenic IBD generally show co-morbidities and/or extraintestinal manifestation at the time of diagnosis, cases of IBD developing as the initial symptom with unremarkable prodromal symptoms have been reported. It is crucial that the physicians properly match genetic analytical data with clinical diagnosis and/or differential diagnosis. In this review, we summarize the essential clues that may physicians make a correct diagnosis of monogenic disease, including classification, prevalence and clinical phenotype based on available literatures.